EXTENSÃO UNIVERSITÁRIA NA EUROPA: A TERCEIRA MISSÃO - Pedro Nunes Teixeira (Universidade Federal da Fronteira Sul, 2015)
In many countries, interest in greater openness and integration of universities to social and economic environment is growing. Driven by society and the knowledge economy and the social demands, the University Extension has gained increasing importance, both in Latin America where the main focus is on direct social actions, interventions promoting citizenship and fomenting local leadership, whether in developed economies where services and technology transfer receive greater attention. In continental Europe the term correlate to the most widely adopted extension is "Third Mission", and is subdivided into three sub-areas: Continuing Education, Technology Transfer and Innovation, and Social Engagement. This Academy playing field also gains strength in the "old continent". Em vários países, o interesse por maior abertura e integração das universidades ao meio social e econômico é crescente. Impulsionada pela sociedade e economia do conhecimento e pelas demandas sociais, a Extensão Universitária ganha cada vez mais importância, seja na América Latina onde o foco principal são ações sociais diretas, intervenções promotoras da cidadania e fomentadoras do protagonismo local, seja em economias mais desenvolvidas onde os serviços e a transferência de tecnologia recebem maior atenção. Na Europa continental o termo correlato à extensão mais adotado é "Terceira Missão" (Third Mission)1, e subdivide-se em três sub-áreas: Educação Continuada, Transferência de Tecnologia e Inovação, e Engajamento Social. Este campo de atuação da academia também ganha força no "velho continente".